Uncovering the Mechanisms of BaBaoWuDanYaoMo Against Influenza A Virus and Virus-Induced Inflammation Based on Network Pharmacology and Pharmacological Evaluation - Lei B; Su Y; Chen R; Chen Z; Liu B; Chen Y; Zhou M; Wang X; Ma Q (Infection and Drug Resistance)
Biao Lei,1,* Yongjie Su,1,* Ruihan Chen,1,* Zexing Chen,1,* Bin Liu,1 Yuou Chen,1,2 Meihua Zhou,1 Xinhua Wang,1,3 Qinhai Ma1 1State Key Laboratory of Respiratory Disease, National Clinical Research Center for Respiratory Disease, Guangzhou Institute of Respiratory Health, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 2King Med School of Laboratory Medicine, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China; 3Institute of Integration of Traditional and Western Medicine, Guangzhou Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qinhai Ma; Xinhua Wang, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China, Email 13268268214@163.com; xinhuaw@gzhmu.edu.cnPurpose: The pro-inflammatory response triggered by influenza viruses can contribute to viral pneumonia, even death. The effect and mechanism of BaBaoWuDanYaoMo (BB) against influenza virus remains obscure. To predict its therapeutic targets via network pharmacology and verify the therapeutic effect and the mechanism of BB against influenza virus in vitro and in vivo.Material and Methods: The potential active and underlying mechanism of BB in the treatment of influenza virus was predicted through network pharmacological strategies and Molecular Docking. The protective and anti-inflammatory effects of BB were determined by cytopathic effect (CPE), quantitative real-time PCR, mitochondrial membrane potentials and Western blotting assay in vitro. BALB/c mice were intranasally infected with A/PR/8/34 (H1N1) (PR8) and orally administrated BB (500 mg/kg, 250 mg/kg and 125 mg/kg) or oseltamivir daily. The normal group was orally administrated PBS for 5 days. Lung indexes, histological changes and cytokines were determined on the 6th day.Results: BB could effectively inhibit A/Puerto Rico/8/1934 (H1N1), A/GZ/GIRD07/09 (H1N1), A/HK/Y280/97 (H9N2) and A/Aichi/68 (H3N2) with IC50 values of 116.5 ± 2.2, 59.86 ± 8.33, 102.87 ± 6.66 and 66.43 ± 6.785 μg/mL, respectively. It could inhibit PR8-induced apoptosis and inhibit the expression of apoptosis markers (cleaved PARP). BB inhibited the mRNA expression of MCP-1/CCL-2, IL-6, CXCL-8/IL-8, TNF-α and CXCL-10/IP-10, and downregulated the protein expression of phosphorylated AKT/p38 and TLR3 in vitro. BB (500 and 250 mg/kg) could improve pulmonary histopathological changes, decrease the lung index and suppress the mRNA expression of CXCL1/KC, TNF-α, CXCL9/MIG and IL-1β in vivo.Conclusion: BB has a protective effect on PR8-induced acute lung injury (ALI) probably via inhibition of apoptosis process and interfering with TLR3, p38 MAPK and PI3K-AKT signaling pathways. This study provided a potential treatment for influenza from BB, and network pharmacology provided a strategy to explore active components and mechanism of TCMs against influenza virus infection. Keywords: influenza, apoptosis, viral pneumonia, acute infectious respiratory disease, traditional Chinese medicines